Role of systems science in preventing and controlling emerging infectious diseases: protocol for a scoping review. Issue 6 (8th June 2021) - Mansouri, Mariam Abdulmonem; Kee, Frank; Garcia, Leandro; Bradley, Declan T
Abstract : Introduction: In recent history, many new infectious diseases have affected humans for the first time or have appeared in previously unaffected areas of the world; these diseases are known as emerging infectious diseases (EIDs). Examples of EIDs include COVID-19, Middle East respiratory syndrome and Ebola virus disease. EIDs are known for their complexity. Multiple factors play a role in their spread, including increases in human population, conflicts, urbanisation, air travel, global trade and inequalities in wealth distribution and access to healthcare. In order to gain a better understanding of such complexity, we aim to explore the role of systems science, which allows us to view EIDs in the context of complex adaptive systems rather than simple causes and effects. The objectives of this scoping review are to explore and map the theoretical concepts and key characteristics of studies that use systems methods in controlling EIDs, to identify the gaps in knowledge and disseminate the results. Methods: We will follow the Joanna Briggs Institute guidance for this scoping review, comprising the following stages: formulating the research question and subquestions, scanning the literature for available data, selecting relevant publications, charting the data by two independent reviewers, aggregating the findings, reporting, summarising and disseminating the results. We will review peer-reviewed articles, preprints and grey literature available in all languages. Discussion: We intend that this scoping review will contribute to a better understanding of the use of systems methods to inform policymakers about how to prevent and control EIDs. Ethics and dissemination: Research ethics approval is not required for a scoping review because it is based on reviewing and collecting data from publicly available sources. To disseminate the findings, results will be shared through academic publications, seminars and conferences.